2016
DOI: 10.1097/j.pain.0000000000000611
|View full text |Cite
|
Sign up to set email alerts
|

Increased fronto-hippocampal connectivity in the Prrxl1 knockout mouse model of congenital hypoalgesia

Abstract: Despite the large number of studies addressing how prolonged painful stimulation affects brain functioning, there are only a handful of studies aimed at uncovering if persistent conditions of reduced pain perception would also result in brain plasticity. Permanent hypoalgesia induced by neonatal injection of capsaicin or carrageenan has already been shown to affect learning and memory and to induce alterations in brain gene expression. In this study, we used the Prrxl1 model of congenital mild hypoalgesia to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 97 publications
2
11
0
Order By: Relevance
“…To explore pain-relevant target genes of the homeobox transcription factor DRGX, we assessed genes whose expression was reportedly changed in the forebrain of DRGX-knockout mice. 22 Among them, we focused on MMP-9 and EP 2 , both of which were increased in DRGX-null forebrain and is involved in neuropathic pain. 23,25,26 Expression levels of MMP-9 and EP 2 were increased in L5 DRG after SNL (Figure 4(a) and (b)).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To explore pain-relevant target genes of the homeobox transcription factor DRGX, we assessed genes whose expression was reportedly changed in the forebrain of DRGX-knockout mice. 22 Among them, we focused on MMP-9 and EP 2 , both of which were increased in DRGX-null forebrain and is involved in neuropathic pain. 23,25,26 Expression levels of MMP-9 and EP 2 were increased in L5 DRG after SNL (Figure 4(a) and (b)).…”
Section: Resultsmentioning
confidence: 99%
“…However, in the medial prefrontal cortex, amygdala, or hippocampus of DRGX-null mice, mRNA levels of dozens of genes were reportedly changed. 22 Therefore, DRGX downregulation-induced pain was most likely mediated by transcriptional regulation of pain-related genes. Consistent with this idea, DRGX downregulation induced upregulation of MMP-9 and EP 2 in the DRG, as well as hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oscillatory interactions across different brain circuits reflect a global state of the system, and are suggested to act as an alert mechanism to identify functional perturbations 37 . In the scope of nociceptive information processing, these perturbations have been reported in the cortico-hippocampal 29,31,44 and cortico-thalamic 30,39,45 circuits in chronic pain patients and in animal models of chronic pain. In this study, an important aspect was the effects of bidirectional optogenetic manipulations of PL-mPFC CaMKIIα-expressing neurons activity in spectral properties.…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal theta ‐oscillations are positively correlated with cognitive and mnemonic processes (Klimesch, ; Tesche and Karhu, ; Royer et al., ; Schmidt et al., ). These theta power oscillations have been also associated to fronto‐hippocampal interactions that facilitate decision‐making processes (Jones and Wilson, ; Onton et al., ; Hyman et al., ), that are disturbed during neuropathic pain (Cardoso‐Cruz et al., ; Monteiro et al., ) and anxiety conditions (Adhikari et al., ). We found that D2r blockade disrupts global theta power oscillations in SNI‐treated animals.…”
Section: Discussionmentioning
confidence: 99%